Hybrid thoracoabdominal aortic aneurysm repair: is the future here? - Orozco-Sevilla, Vicente (J Vis Surg, 2018)
Open surgical repair has been the gold standard for thoracoabdominal aortic aneurysm (TAAA) repair for more than 6 decades, but 2 additional options have emerged: total endovascular TAAA repair and a hybrid approach that combines open and endovascular repair. Despite the optimism for an endovascular approach, long-term results for these repairs are still lacking. Some of the issues with this emerging technology include the risk of paraplegia after extensive endovascular repair, the need for multiple reinterventions, continuous stent-graft surveillance, endograft branch stenosis, as well as the significant learning curve. Interest in a hybrid approach has resurged despite the non-superior results compared to open TAAA. Commonly, the focus of the hybrid approach is now on performing a less extensive open TAAA repair, which is then extended with a stent-graft or vice versa. Moreover, this approach is now often performed in two stages in an effort to decrease the associated spinal cord ischemia. Open surgical repair after endovascular aortic repair is increasingly being performed to address serious complications, such as infection or fistula, that cannot be repaired by further endovascular intervention. As with any new technology, there will be an increase in the number of procedure-related complications and a decrease in the number of surgeons who can perform the traditional open operation with good results.